The success of learnerships? Lessons from South Africa's training and education programme - Neil Rankin; Gareth Roberts; Volker Schöer (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Vocational training programmes, like South Africa's learnership programme, which combine classroom learning and on-the-job training seem like the type of intervention which can create skills, get young people into jobs quicker, and reduce youth unemployment. This paper uses a longitudinal dataset of young people over four years - some of whom participate in the learnership programme - and firm level data to assess whether the programme meets its objectives, and based on this draws lessons for similar programmes in other countries. The results are disappointing: young people completing learnerships are more likely to be employed but this fades quickly; they do not get better jobs; and the way the programme is funded, as well as the nature of the firms which undertake subsidized training, means that the programme redistributes resources from smaller to larger firms and from more labour-intensive firms to less.
Keywords: I25; I28; J24; O15; 330; vocational training; youth employment; South Africa; learnerships